Estado nutricional de pacientes portadores de doença renal crônica terminal em hemodiálise - Dobner, Taise (2013)
The nutritional status of patients on hemodialysis should be measured consistently through different markers, as they are people with changes that affect in a complex way their nutrients intake and body composition. The aim of this study was to evaluate the prevalence of nutritional disorders and the factors related to it in patients with end-stage renal disease on hemodialysis. This is a cross-sectional study carried out at an institution from northern Rio Grande do Sul with 90 patients. Anthropometric measurements were done after the dialysis section, with the exception of the weight, which was measured before and after. One evaluated: weight, body index mass, interdialytic weight gain, arm muscle circumference, arm muscle area, arm fat area, triceps, biceps, suprailiac and subscapular skinfolds and adductor pollicis muscle. The laboratory tests were collected by the hospital s laboratory professionals according to the hemodialysis service routine. The food consumption was measured through 24/7 written and photographic records for better accuracy of the portions, subsequently one assessed the Healthy Eating Index for the Brazilian population. This thesis is structured in two scientific productions, the first of which brings the nutritional status by anthropometry and laboratory examinations of patients. The second presents the scientific output power of patients through the Healthy Eating Index revealing its association with biochemical, anthropometric and socioeconomic markers. The data demonstrate the need for nutrition education and constant monitoring of these patients, guaranteeing a better life quality, proper and individualized treatment, being the interdisciplinary work very important in this process